Ex Vivo Product Distribution of Injectable Biostimulator Substances. (20th January 2023) - Casabona, Gabriela; Alfertshofer, Michael; Kaye, Kai; Frank, Konstantin; Moellhoff, Nicholas; Davidovic, Kristina; Cotofana, Sebastian
Abstract: Background: Increasing demand for minimally invasive aesthetic treatments, such as injection of biostimulator substances to induce the production of extracellular matrix, has been reported. Recent studies have reported on a variety of different product characteristics influencing the integration and distribution of biostimulator substances after injection. Objectives: The aim of this study was to analyze the ex vivo product integration and distribution behavior of 6 different biostimulator substances after injection. Methods: A total of n = 21 abdominal soft tissue flaps were analysed by real-time ultrasound imaging with regards to horizontal and vertical spread of 6 different injected biostimulator substances—based on hydroxylapatite (HA), polycaprolactone (PCL), and poly-L-lactic acid (PLLA)—immediately after injection and after massaging. The 6 different biostimulator substances were R-CaHA-based, H-CaHA-based, PCL-based, PLLA-1-based, PLLA-2-based and H-HA-based products. Results: Overall, the R-CaHA-, H-CaHA-, and PCL-based substances showed greater product spread after massaging when compared with the product distribution immediately after the injection with all P < .001 with the exception of the vertical dimension of the H-CaHA-based substance ( P = .064). The PLLA-1-, PLLA-2-, and H-HA-based substances showed smaller product spread after massaging compared with the product distribution immediately after the injection with all P < .001 with the exception of the horizontal dimension of the H-HA-based substance ( P = .314), indicating higher tissue integration. Conclusions: Different biostimulator substances behave differently when injected into subcutaneous soft tissues; differences exist at the level of initial product diffusion and during tissue integration.